Innovation and Digital Business Literacy for Agriculture Sector - Muhlis, Muhlis; Hasan, Muhammad; Ahmad, Muh. Ihsan Said; Rahma, Nur Aliah (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2025)
This study was conducted with the aim of determining the development of digital business literacy activities in agricultural management in Makassar City carried out by KT Cokonuri. This study was conducted in Gunung sari Village, Makassar City. The development of digital business literacy is suitable to be studied to measure the extent of development carried out by the KT Cokonuri Farming business. The research method used in this study is to use a qualitative research method with descriptive use. This study uses data collection techniques through field observation and interview methods. The informants in this study numbered three people, namely the chairman, treasurer, and also the field extension worker at KT Cokonuri. Informant sampling was used using the purposive sampling technique. This study shows that there is still a lack of development of digital business literacy carried out by KT Cokonuri members. Digital business literacy is only carried out if there are training activities by instructors and is not carried out routinely. The development that needs to be carried out is more related to digital business literacy activities, including (1) utilizing technology, (2) conducting routine socialization related to digital business, and (3) overcoming obstacles by adding facilities to support literacy activities. Keywords: innovation development, digital business, agriculture